Aquatic Toxicology Notes: Endothall - P. Chris Wilson; Jun Wu (EDIS)
Endothall is the herbicidal active ingredient found in commercial formulations labeled for weed control in aquatic systems and on ditch banks. It is also used as a defoliant and desiccant in some terrestrial situations (e.g., in potato, hops, cotton, clover, and alfalfa production). This 7-page fact sheet introduces users of endothall to the physical, chemical, environmental, and ecological properties of this herbicidal active ingredient relative to the aquatic environment. Written by P. Chris Wilson and Jun Wu, and published by the UF Department of Soil and Water Science, October 2012.